Prevalence of 25-hydroxyvitamin D deficiency in Korean adolescents: association with age, season and parental vitamin D status. Issue 1 (26th October 2012) - Kim, Shin Hye; Oh, Min Kyung; Namgung, Ran; Park, Mi Jung
Abstract: Objective: We aimed to assess the prevalence and associated factors of vitamin D deficiency in healthy adolescents and to determine parent–adolescent association in vitamin D status. Design: A cross-sectional study. Setting: Data from the Korean National Health and Nutrition Examination Survey (KNHANES) 2008–2009. Serum 25-hydroxyvitamin D (25(OH)D) levels were measured using 125 I-labelled RIA kits. Vitamin D deficiency in adolescents was defined as 25(OH)D level <27·5 nmol/l, and 25(OH)D levels between 27·5 and <50 nmol/l were considered insufficient. For the parents, vitamin D deficiency was defined as 25(OH)D level <50 nmol/l. Subjects: The study population consisted of 2062 adolescents (1095 boys, 967 girls; aged 10–18 years) and their parents (1005 fathers, 1341 mothers). Results: Overall, 13·4 % of adolescents (boys 11·7 %, girls 15·4 %) were 25(OH)D deficient, 54·7 % were 25(OH)D insufficient. Prevalence of vitamin D deficiency increased with age ( P < 0·0001). Parental vitamin D deficiency was more prevalent in vitamin D-deficient adolescents than in non-deficient adolescents (all P < 0·0001). In multivariate logistic regression analyses, predictors for vitamin D deficiency were senior high school students (OR = 3·45–4·33), winter/spring season (OR = 3·18–5·11/5·35–7·36) and parental vitamin D deficiency (OR = 1·78–4·88; all P < 0·05). Conclusions: Vitamin D insufficiency is prevalent among healthy Korean adolescents and the parent–offspring association warrants vitamin D screening for family members of deficient individuals.